Magnesium Sulfate as a Second-Line Tocolytic Agent for Preterm Labor: A Randomized Controlled Trial in Kyushu Island - Yasuyuki Kawagoe; Hiroshi Sameshima; Tsuyomu Ikenoue; Ichiro Yasuhi; Tatsuhiko Kawarabayashi (Journal of Pregnancy)
Objectives. We evaluated the efficacy of magnesium sulfate as a second-line tocolysis for 48 hours. Materials and Methods. A multi-institutional, simple 2-arm randomized controlled trial was performed. Forty-five women at 22 to 34 weeks of gestation were eligible, whose ritodrine did not sufficiently inhibit uterine contractions. After excluding 12 women, 33 were randomly assigned to either magnesium alone or combination (ritodrine and magnesium). The treatment was determined as effective if the frequency of uterine contraction was reduced by 30% at 48 hours of the treatment. Results. After magnesium sulfate infusion, 90% prolonged their pregnancy for >48 hours. Combination therapy was effective in 95% (18/19), which was significantly higher than 50% (7/14) for magnesium alone. Conclusion. This randomized trial revealed that combination therapy significantly reduced uterine contractions, suggesting that adjuvant magnesium with ritodrine is recommended, rather than changing into magnesium alone, when uterine contractions are intractable with ritodrine infusion.